A IMPLEMENTATION OF GREEN SUKUK IS BASED ON THE DSN-MUI FATWA NO: 137/DSN-MUI/IX/2020 - Munirah, Azizah (UMBanjarmasin, 2024)
The important role of sukuk as a source of funding to support national development and a Sharia-based investment instrument in Indonesia has been widely researched and published in various scientific articles. Research on sukuk in Indonesia also continues to increase, from 2010 to 2021there were 47 articles. Increased research on sukuk provides in-depth analytical knowledge aboutthe importance and benefits of Sukuk investment both individually and nationally. In order to develop sharia capital market industries and products in Indonesia, including sukuk-based products, large amounts of funding are needed to participate in investment activities for economicneeds in Indonesia. This article uses qualitative research with data collection techniques such assearching for journals, articles and books that discuss Green Sukuk. After collecting data sources,the author will analyze and draw conclusions as a result of the research. The aim of this researchis to find out how to implement green sukuk based on DSN-MUI Fatwa Number 32IDSN- MUIIIX/2002 concerning Sharia Bonds (also known as Sukuk). This research also finds out aboutthe considerations that DSN-MUI considers it necessary to establish a fatwa on Sukuk to serve as a guideline.